An Employment Law Clinic: Developing of Student's Capacity through Clinical Legal Education in Employment Matters on ASEAN Economic Community Era - Sulistiyono, Tri; Arifin, Ridwan (Faculty of Law Universitas Negeri Semarang, 2019)
The legal clinic, a pivotal component of law school programs, offers law students valuable practical experience while providing pro bono legal services to diverse clients. In the context of the ASEAN Economic Community (AEC) Era, the challenges posed to regional communities, especially Indonesia, in navigating a free trade area underscore the importance of legal education in employment law. Given the heightened trade activities, a profound understanding of employment law becomes essential not only for practitioners but also for students and law school graduates. In response to the changing landscape, an employment law clinic emerges as a crucial resource, offering free legal advice on various employment matters to address the escalating drop in claims due to the introduction of employment fees. This service becomes indispensable in mitigating non-litigated violations of employment law resulting from financial barriers. This paper explores three key aspects: first, the role of an employment law clinic in law school legal education as a foundational preparation for the AEC era; second, its utilization by students to enhance their capacity in employment matters; and third, its provision of legal services in the international trade law context, particularly focusing on labor and employment law issues. Emphasizing employment law issues such as illegal pay deductions, employment discrimination, unfair dismissal, zero-hour contracts, and trade union freedom in Southeast Asia, the paper advocates for collaboration between the clinic, companies, governments, practitioners, and lawyers to ensure its effectiveness and relevance.